Bacterial synthesis of a novel human leukocyte interferon. - Yelverton, E (1981)
A novel human leukocyte interferon cDNA clone (LeIF B) was identified in a cDNA library prepared using polyadenylated mRNA of a myeloblastoid cell line. The nucleotide sequence of LeIF B differs significantly from other published leukocyte interferon cDNA sequences. An expression plasmid was constructed which directs the synthesis in E. coli of 8 x 10(7) interferon units per liter of culture. LeIF B exhibits markedly different specificities from another bacterially synthesized human leukocyte interferon, LeIF A.